Cycle Link : procurement in Europe - Yue, Tao, active 2012, (SAGE Business Cases., 2012)
Cycle Link Europe moved its European headquarters to Rotterdam, the Netherlands, in 2011 after experiencing difficulties in Germany. The company purchased and exported recovered paper from Europe to China for its own production needs. Its strategy in Europe was to outperform competitors in service areas by implementing timely pickup of goods, continual purchase, and in-time payment tactics. Since superior service was a competitive advantage, Cycle Link Europe needed good people and reliable suppliers. However, working with Western employees and suppliers did not always run smoothly - communication sometimes experienced glitches.